2017
DOI: 10.1039/c7cp03960c
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals heterostructures based on allotropes of phosphorene and MoSe2

Abstract: The van der Waals heterostructures of allotropes of phosphorene (α-and β-P) with MoSe2 (H-, T-, ZT-and SO-MoSe2) are investigated in the framework of state-of-the-art density functional theory.The semiconducting heterostructures, β-P /H-MoSe2 and α-P / H-MoSe2, forms anti-type structures with type I and type II band alignments, respectively, whose bands are tunable with external electric field. α-P / ZT-MoSe2 and α-P / SO-MoSe2 form ohmic semiconductor-metal contacts while Schottky barrier in β-P / T-MoSe2 can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 43 publications
2
15
1
2
Order By: Relevance
“…It indicated that they possess an inherent electric dipole moment with magnitude 0.075 V/Å and 0.025 V/Å respectively, whose direction depends on materials internal electrostatic potential. Surprisingly, magnitude of electric field causing phase transition of PN/PAs-WSe 2 heterostructures are much smaller than recently reported BP-MoSe 2 vdW heterostructure of 1 V/Å 23 and BP-MoSSe vdW heterostructure of 0.8 V/Å 22 . The projected band structures of the PN-WSe 2 vdW heterostructures with different electrical field are presented from Fig.…”
Section: Resultscontrasting
confidence: 63%
“…It indicated that they possess an inherent electric dipole moment with magnitude 0.075 V/Å and 0.025 V/Å respectively, whose direction depends on materials internal electrostatic potential. Surprisingly, magnitude of electric field causing phase transition of PN/PAs-WSe 2 heterostructures are much smaller than recently reported BP-MoSe 2 vdW heterostructure of 1 V/Å 23 and BP-MoSSe vdW heterostructure of 0.8 V/Å 22 . The projected band structures of the PN-WSe 2 vdW heterostructures with different electrical field are presented from Fig.…”
Section: Resultscontrasting
confidence: 63%
“…Monolayer green-P is a semiconductor with a direct bandgap of ~1.35 eV. The direct nature of the bandgap is preserved on moving from monolayer to bilayer but the magnitude of bandgap decreases to 1.17 It is well known that electric field and pressure can effectively tune the electronic properties of 2D materials [35,36]. On applying perpendicular electric field in bilayer green phosphorene, a systematic shift in both VBM and CBM has been found [Figure 3 is feasible in real experimental situation.…”
Section: Effect Of Thickness Electric Field and Pressure On Band Gapmentioning
confidence: 99%
“…38 It has well-built physical anisotropy and high conductance that nds applications in the eld of nano-electronics and optoelectronics. 39 Not only multi-layered but single-layered black phosphorene have also been successfully exfoliated. 9,[40][41][42] Previous research works have shown that black phosphorene has good carrier mobility and has direct bandgap.…”
Section: Introductionmentioning
confidence: 99%